Synthesis and characterization of titanium dioxide nanoparticles from Bacillus subtilis MTCC 8322 and its application for the removal of methylene blue and orange G dyes under UV light and visible light - Rathore, Chandani; Yadav, Virendra Kumar; Amari, Abdelfattah; Meena, Abhishek; Chinedu Egbosiuba, Titus; Verma, Rakesh Kumar; Mahdhi, Noureddine; Choudhary, Nisha; Sahoo, Dipak Kumar; Chundawat, Rajendra Singh; Patel, Ashish (Frontiers in Bioengineering and Biotechnology, 2024)
Over the last decade there has been a huge increase in the green synthesis of nanoparticles. Moreover, there is a continuous increase in harnessing the potential of microorganisms for the development of efficient and biocompatible nanoparticles around the globe. In the present research work, investigators have synthesized TiO2 NPs by harnessing the potential of Bacillus subtilis MTCC 8322 (Gram-positive) bacteria. The formation and confirmation of the TiO2 NPs synthesized by bacteria were carried out by using UV-Vis spectroscopy, Fourier transforms infrared (FT-IR), Xray diffraction (XRD), scanning electron microscope (SEM), and energy dispersive X-ray spectroscopy (EDX/EDS). The size of the synthesized TiO2 NPs was 80-120 nm which was spherical to irregular in shape as revealed by SEM. FTIR showed the characteristic bands of Ti-O in the range of 400-550 cm -1 and 924 cm -1 while the band at 2930 cm -1 confirmed the association of bacterial biomolecules with the synthesized TiO2 NPs. XRD showed two major peaks; 27.5° (rutile phase) and 45.6° (anatase phase) for the synthesized TiO2 NPs. Finally, the potential of the synthesized TiO2 NPs was assessed as an antibacterial agent and photocatalyst. The remediation of Methylene blue (MB) and Orange G (OG) dyes was carried out under UV-light and visible light for a contact time of 150 to 240 minutes respectively. The removal efficiency for 100 ppm MB dye was 25.75% and for OG dye was 72.24% under UV light, while in visible light, the maximum removal percentage for MB and OG dye was 98.85% and 80.43% respectively at 90 minutes.Moreover, a kinetic study and adsorption isotherm study were carried out for the removal of both dyes, where the pseudo-first-order for MB dye is 263.269 and 475554.176 mg/g for OG dye. The pseudo-second-order kinetics for MB and OG dye were 188.679 and 1666.667 mg/g respectively.In addition to this, the antibacterial activity of TiO2 NPs was assessed against Bacillus subtilis MTCC 8322 (Gram-positive) and Escherichia coli MTCC 8933 (Gram-negative) where the maximum zone of inhibition in Bacillus subtilis MTCC 8322 was about 12 mm, and for E. coli 16 mm.